Challenges and changes in Indian rural credit market: a review. Issue 3 (3rd June 2019) - Ray, Sougata
Abstract : Purpose: Post-independence, the rural credit market in India has undergone significant structural changes in order to enhance the availability and efficient use of credit. The purpose of this paper is to understand the challenges and changes in the Indian rural credit market in the post-independence period. Design/methodology/approach: Using data from the All India Debt and Investment Survey conducted by the National Sample Survey Organisation of the Government of India from 1971–1972 to 2012 and Reserve Bank of India in 1951–1952 and 1961–1962, the study focuses on three important aspect of rural credit market, i.e. the availability, sources and uses of credit. The analysis is based on both the national and state level data and uses the decadal growth rates to explain the changes in the rural credit market. Findings: Availability of credit, in terms of volume and number of households indebted, has increased substantially. However, the sharp rise in outstanding debt is a matter of concern. The share of credit from institutional agencies has seen a continuous decline post liberalisation. The non-institutional agencies, particularly the professional moneylenders, continue to be the most preferred sources of credit owing to their flexible nature of operation. Interesting, microfinance has emerged as a major source of credit particularly for the poor rural households. The rise in credit usage for non-income generating activities amongst poor households is another important concern. Originality/value: The study highlights some of the most important features and characteristics associated with the Indian rural credit market. An understanding of these issues would provide valuable insight for shaping the future policy responses.